Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. IV. Carburetors-Clutch (H.S. Stuttman Co, 1975)
469-622 p.; 25 cm.